The distortionary effects of unconstrained for-profit carbon dioxide removal and the need for early governance intervention - Emily Grubert; Shuchi Talati (Carbon Management)
Carbon Dioxide Removal (CDR) is an emerging activity with extremely limited deployment to date, but which is mathematically required to achieve net (rather than true) zero or negative anthropogenic contribution to climate change. The required scale of CDR, however, depends on decisions about what activities will be allowed to emit greenhouse gases – the “residual emissions” that must be compensated via CDR. Simultaneously, CDR’s availability is limited by resource needs and feasibility, much like conventional depletable resources. Governance and institutions, especially related to how CDR is allocated and paid for, will fundamentally shape CDR efforts, including by structurally incentivizing particular approaches and monitoring, reporting, and verification (MRV) objectives. We argue that the emerging tendency toward market-based, unconstrained, and for-profit CDR presents fundamental and predictable risks for climate and justice goals. Such a model incentivizes growth in profitable compensatory removal applications, effectively allocating limited resources based on ability to pay rather than public good, while also increasing the amount of CDR required to meet global climate targets. “Luxury” removals that could otherwise be mitigated not only displace, but actively disincentivize deployment for compensatory removals in high priority but low wealth applications, and for drawdown. Meeting these needs would likely become a socialized cost. Markets also establish unit-level property rights that require specific kinds of MRV that are misaligned with climate outcomes and face incentives for poor quality verification. We describe the need, development context, function, and resource limitations of CDR, then characterize the major challenges with the emerging unconstrained, for-profit governance model. We argue that instead implementing CDR as a centrally planned sector, with publicly deliberated and adaptable volumetric targets integrated with other climate action, could enable more just and effective outcomes.